2010
DOI: 10.1016/s0924-9338(10)70758-6
|View full text |Cite
|
Sign up to set email alerts
|

P02-144 - Subjective Well-being Under Neuroleptics (SWN): a Predictor of Clinical and Psychosocial Outcome in Acute Patients. Preliminary Data

Abstract: Objectives: To evaluate the subjective well-being of a group of patients who were hospitalized at the Institute of Psychiatry (Novara), compared to the severity of illness. Methods: Patients are evaluated at admission and discharge through self-administration of the SWN (Subjective Well-being under Neuroleptics) scale, which contains five subscales (emotional regulation; self-control; mental functioning; social integration and physical functioning) assessing patients' psychophysical and emotional well-being, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is because of this perspective that it is widely used in studies evaluating patients' quality of life, responses to antipsychotic treatment and drug side-effects (1,5,11,12). Some studies have reported that the score on the Subjective Well-Being Under Neuroleptics Scale is a good predictor of treatment response indicators, such as entering remission (9,13), drug compatibility (14), and quality of life (9,15). The original 38-item form of the scale was designed by Naber (1995) (10), who also developed a shortened, 20-item form (SWNS) (3).…”
Section: Introductionmentioning
confidence: 99%
“…It is because of this perspective that it is widely used in studies evaluating patients' quality of life, responses to antipsychotic treatment and drug side-effects (1,5,11,12). Some studies have reported that the score on the Subjective Well-Being Under Neuroleptics Scale is a good predictor of treatment response indicators, such as entering remission (9,13), drug compatibility (14), and quality of life (9,15). The original 38-item form of the scale was designed by Naber (1995) (10), who also developed a shortened, 20-item form (SWNS) (3).…”
Section: Introductionmentioning
confidence: 99%